Synthesis of Silica-Salen Derivative from Rice Husk Ash and its Use for Extraction of Divalent Metal Ions Co(II), Ni(II) and Cu(II) - Duha Hussien Attol; Hayder Hamied Mihsen (Indonesian Journal of Chemistry, 2020)
Rice husk ash (RHA) was used to prepare sodium silicate, which in turn was functionalized with 3-(chloropropyl)triethoxysilane employing the sol-gel technique to form RHACCl. Chloro group in RHACCl was replaced with iodo group forming RHACI. Ethylenediamine was immobilized on RHACI in order to prepare it for the reaction with salicylaldehyde to form a silica derivative-salen. FT-IR analysis indicated the presence of secondary amine and –NH and C=N absorption bands. XRD analysis revealed the occurrence of the broad diffused peak with maximum intensity at 22–23° (2θ). BET measurements showed also that the surface area of the prepared compound is 274.55 m2/g. Elemental analysis proved the existence of nitrogen in the structure of the prepared compound. The silica derivative-salen showed high potential for extraction and removal of heavy contaminating metal ions Ni(II), Cu(II), and Co(II) from aqueous solutions. The kinetic study demonstrates that the adsorption of the metal ions follows the pseudo-second order.